PENGEMBANGAN E-BOOK INTERAKTIF MENGGUNAKAN APLIKASI FLIP BOOK MAKER PADA MATA PELAJARAN TIK DI SMPN 5 SATAP MANGGELEWA - Agus Setiawan; Muslim; Muslimin , Ikhwannul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low student learning outcomes and the limited use of interactive digital learning media in the learning process. The purpose of this study was to develop an interactive e-book learning media using the Flip Book Maker application for the Information and Communication Technology (ICT) subject at SMP Negeri 5 Satap Manggelewa. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The product developed was an interactive e-book integrating text, images, videos, animations, and interactive navigation features to support ICT learning. The research subjects consisted of eighth-grade students of SMP Negeri 5 Satap Manggelewa. The feasibility of the product was evaluated through validation by material experts and media experts, while its practicality and effectiveness were measured using student response questionnaires and learning achievement tests. The results showed that the developed learning media obtained an average media expert validation score of 87% and a material expert validation score of 90%, both categorized ashighly feasible. The implementation results indicated an improvement in the students' average score from 52 in the pre-test to 80.00 in the post-test. The N-Gain analysis produced scores ranging from 0,052% to 58%, indicating ahigh level of effectiveness. These findings demonstrate that the interactive e-book developed using the Flip Book Maker application is effective for ICT learning at SMP Negeri 5 Satap Manggelewa. Therefore, the developed learning media can serve as an innovative digital learning resource that effectively improves students' learning outcomes.